Effectiveness Analysis Using Overall Equipment Effectiveness (OEE) and Failure Modes And Effect Analysis (FMEA) Methods at PT. XYZ - Rangga Firmansyah Armaputra; Said Salim Dahda (Universitas Islam Raden Rahmat, Malang, 2025)
PT. XYZ is a manufacturing company engaged in the production of NPK fertilizer. During its production process, the company frequently encounters machine downtime issues that significantly affect overall production effectiveness. This study aims to evaluate machine performance effectiveness using the Overall Equipment Effectiveness (OEE) method by assessing three key components: Availability, Performance, and Quality, as well as to identify the dominant sources of failure through Failure Mode and Effect Analysis (FMEA). Data were analyzed using Microsoft Excel through descriptive and comparative approaches to calculate the average OEE value, identify the contribution of the Six Big Losses, and determine the Risk Priority Number (RPN) in FMEA. The results show that the average OEE value was 83%, consisting of Availability 76%, Performance 110%, and Quality 99.8%, which remains below the Japan Institute of Plant Maintenance (JIPM) standard of 85%. The largest loss factor originated from idling and minor stoppages, contributing 38.2% of total production losses. FMEA analysis identified the most critical failure mode in the gearbox/fluid coupling of the conveyor, with the highest RPN value of 448.3, caused by mechanical wear and insufficient periodic inspections. Based on these findings, it is recommended to implement a scheduled preventive maintenance program, ensure the availability of critical spare parts, and enhance operator competence in machine operation and monitoring to improve the overall production system effectiveness.